Structural Bioinformatics of Proteins: Predicting the Tertiary and Quaternary Structure of Proteins from Sequence - Oliva, Baldo; Planas-Iglesias, Joan; Bonet, Jaume; Marín-López, Manuel A.; Feliu, Elisenda; Gursoy, Attila (IntechOpen, 2012)
None